Antalya Körfezi’nden Parazitik Isopodlar (Anilocra frontalis H. Milne Edwards, 1830 ve Ceratothoa capri (Trilles, 1964)) ve Yeni Konakçı Kayıtları - Başusta, Nuri; Mutlu, Erhan; Deval, Mehmet Cengiz (Fırat University, 2017)
Bu çalışmada, Antalya Körfezi’nde 2015 Şubat ayında trol avcılığı ile bazı balıklardan parazitik isopodlar (Anilocra frontalis ve Ceratothoa capri ) toplandı. Bu isopodlar yassı solungaçlılar (Elasmobranch) üzerinde ilk defa gözlendi. Bu üç konakçı (Raja miraletus, Sphyraena sphyraena, Spicara maena) A. frontalis ve C. capri için yeni konakçılardır.

In this study, parasitic isopods Anilocra frontalis and Ceratothoa capri were collected from some fishes by trawling in Antalya Bay, in February, 2015. These isopods were observed on the elasmobranch for the first time. Three of these hosts (Raja miraletus, Sphyraena sphyraena, Spicara maena) are new hosts for A. frontalis and C. capri
Parasitic isopods (Anilocra frontalis H. Milne Edwards, 1830 and Ceratothoa capri (Trilles, 1964)) from the Antalya Bay (Turkey) with new host records
Keywords: Engineering; Mühendislik